The Use of Islamic Patterned Art Therapy: Healing of Psychological Problems Among University Students - Hajra, Bibi (Journal of religion and health, 2021)
This study was designed to adopt art therapy from an Islamic perspective by adding/including shapes and designs of Islamic origin. This was basically color therapy and was designed to find its effectiveness in reducing depression, anxiety. Stress and enhancing psychological well-being of university students with high and low-religious levels from Islamabad and Rawalpindi. This study was carried out in two phases. The first phase was to develop Islamic adult coloring book with Islamic patterns and calligraphy. The second phase was the main study, and it was an experimental study which included screening out a sample, consisting of mild to moderate levels of depression, anxiety and stress and high and low-religiosity levels. A sample of 60 university students received Islamic patterned art therapy. On the basis of religiosity, two groups were formed as either a high-religious group or a low-religious group with individuals in both groups completing fourteen sessions. Pre- and post-test assessments were undertaken via the psychometric tools DASS-21, psychological well-being scale and religiosity scale. Statistics from the independent sample t-test and paired sample t-test and repeated measures ANOVA for within group and between group comparisons, revealed that there was a significant difference from pre-test to post-test assessments of depression anxiety and stress and psychological well-being, whereas there were nonsignificant gender differences on the bases of high and low-religiosity levels. Therefore, it could be concluded that Islamic patterned art therapy was found effective in reducing depression anxiety stress and increasing psychological well-being of university students.